REDUKCINIS EMPIRIZMAS -- METODOLOGIJA AR EPISTEMOLOGIJA? - Bujokas, Justas (Problems / Problemos)
The philosophy of reductive empiricim and its impact on the contemporary debates in the analytic philosophy of science are analysed in this paper. Reductive empiricism, mostly associated with the philosophy of science of logical positivism, aims to show, how theoretical terms can be reduced to the observational terms, thus eliminating the former from the language of science. Reductive empiricism is often considered to be a type of semantic scientific antirealism, which is unsuccessful due to the inner flaws of the idea of theoretical terms reduction to observational terms, for example, unsuccessful application of Bertrand Russell logical formalism or hidden presuppositions of verificationism. I argue, that reductive empiricism, as a part of programme of early logical positivism, fails not because of the idea of theoretical terms reduction to the observational terms itself, but because of hidden assumption, that successful reduction immediately implies the epistemology of empiricism. I suggests that the clear distinction between the reduction, as the method of philosophy, suitable both for realism and empiricism, and empiricism, which ir not neccessarily based on the method of reduction, should be drawn.